Roles of High-Density Lipoprotein Cholesterol in Patients With Acute Myocardial Infarction. Issue 18 (May 2016) - Lee, Cheol Hyun; Woo, Jong Shin; Park, Chang Bum; Cho, Jin Man; Ahn, Young Keun; Kim, Chong Jin; Jeong, Myung Ho; Kim, Weon; ,
Abstract : Abstract: Many observational studies showed hogh-density lipoprotein cholesterol (HDL-C) is a strong inverse predictor of cardiovascular (CV) outcome. However, recent large clinical trials evaluating therapies to raise HDL-C level in those already on statin therapy have been discouraging. This complexity is not well-known. A total of 28, 357 acute myocardial infarction (AMI) patients were enrolled in the Korea Acute Myocardial Infarction Registry (KAMIR), which was a prospective, multicenter, nationwide, web-based database of AMI in Korea. From this registry, we evaluated 3574 patients with AMI who have follow-up HDL-C level to investigate its association with clinical outcomes. The primary endpoint was the relationship between follow-up change in HDL-C and a 12-month composite of major adverse cardiac events (MACEs). Patients with initial HDL-C ≥ 40 mg/dL showed significantly lower rates of 12-month MACEs, especially cardiac and all-cause mortalities ( P  < 0.001). When patients were stratified into 4 groups according to the change of HDL-C, patients with decreasing HDL-C showed significantly higher rates of 12-month MACEs as comparable with patients with increasing HLD-C. A multivariate analysis indicated that HDL-C level was a significant predictor of CV events (hazard ratio, 1.38; 95% confidence interval, 1.12–1.71) after correcting for confounding variables. The follow-up change in HDL-C level was significantly related with CV outcomes in patients with AMI.